THE NATIONALITY OF THE ARBITRAL SENTENCE IN INTERNATIONAL ARBITRATION - Stănescu, Dr. Șerban-Alexandru; Dimofte, Drd. Ana-Maria (PEOPLE: International Journal of Social Sciences, 2024)
In the case of international disputes resolved by means of arbitration, the cross-border effects of the awards are essential for the parties. At first glance, these awards are assimilated to the national court judgements of the state where they were pronounced and are considered foreign court judgements in any other state. Nevertheless, in some cases, the links between the arbitral procedures and the place of pronouncement of the awards are weak or even non-existent, which raises serios doubts over the ability of this specific place to determine the nationality of the arbitral award. The described circumstance is the premise of the present scientific approach, which aims to deepen the analysis of the criteria for determining the nationality of an arbitral award (by a Romanian court), with implications on its cross-border effects, as well as on the procedures that could lead to its dissolution. From a methodological point of view, the research aims, successively, to inventory the applicable legal instruments, to delineate the solutions offered by them, in order to, finally, by overlapping them, provide a comprehensive theory on the determination of the nationality of an arbitral award.